What do we think we’re doing? - Meinwald, Constance (PLATO JOURNAL, 2017)
I suggest that there are no universally applicable principles (in the strong sense) for the study of Plato’s philosophy. Different students of Plato have different objects of interest (e.g. what the individual Plato ultimately thought vs what emerges from thinking about his texts) that can make different ways of proceeding appropriate. For me the dialogues are the main object of study; I think they are best approached by interpreting literary elements and obviously philosophical content as working together. The paper includes illustrations of how parts of my picture of the developing theory of forms emerge from this type of engagement.